Minimally invasive surgery in older children with Hirschsprung’s disease in a North African Country - Arafa, Ahmed; Ragab, Moutaz; Abdelazim, Osama; Khedr, Sayed; Mohamed, Wesam (Frontiers in Surgery, 2022)
Introduction: Hirschsprung’s disease is a bowel congenital anomaly affecting mainly enteric nervous system of the rectosigmoid region. Surgical resection of the aganglionic segment and restoration of bowel continuity via colo-anal anastomosis is the main stay of treatment. In 1999, Georgeson et al. introduced a new minimal invasive approach as a standard for the pull through. This study aims to compare the outcome of laparoscopic-aided transanal pull-through and laparoscopic Duhamel procedure for management of HSD in older children. Methods: This study was performed on 20 patients diagnosed with HSD. The patients are older children, whose mean age is three years old. We excluded from this study the cases showing enterocolitis or obstruction. We divided these cases into two Groups: Group A, consisting of 10 cases where laparoscopic-aided transanal pull-through was done, and Group B, in which laparoscopic Duhamel procedure was done. Results: We have compared between two Groups for the 1st year follow up period, in Group A, there are two cases of stenosis that respond to regular dilation: One case of enterocolitis, one case of fecal incontinence. Whereas, in Group B, we had two cases of constipation, three cases of enterocolitis, there was no anastomotic leak in both Groups. Conclusion: Minimal invasive surgery is safe in management of HSD in older children as one stage, either by using Duhamel procedure or transanal Swenson’s.